Analisis Implementasi Rekam Medis Elektronik Pada Efektivitas Pelayanan di RSUD Depati Hamzah Pangkalpinang - Selviana Selviana; Taufik Kurrohman; Masagus M. Hakim; Dedek Sutinbuk; Heru Listiono (Varied Knowledge Journal, 2026)
This study analyzed the implementation of Electronic Medical Records (EMR) in supporting service effectiveness at Rumah Sakit Umum Daerah Depati Hamzah Pangkalpinang. The study was motivated by the need for accurate, fast, integrated, and secure patient information management in hospital services. A qualitative descriptive approach was used with data collected through in-depth interviews, observation, and document review. Eleven informants who were directly involved in the use and management of EMR were selected purposively. The analysis focused on input, process, and output aspects, including human resources, technology, policy, funding, planning, organizing, implementation, supervision, and service outcomes. The findings showed that EMR implementation supported service effectiveness by accelerating access to patient information, improving administrative efficiency, reducing paper-based records, supporting inter-unit coordination, and improving the quality of medical record data. However, several obstacles remained, including unstable networks, uneven user competence, incomplete data entry, limited integration of electronic signatures, and the need for stronger monitoring. Therefore, EMR implementation requires continuous improvement through user training, infrastructure strengthening, policy reinforcement, system development, and regular evaluation to ensure that EMR contributes optimally to hospital service quality.